Analisis Potensi Partnership sebagai Moda untuk meningkatkan Kapabilitas Inovasi dan Teknologi - Jane, Orpha (Business Administration Study Program - Universitas Katolik Parahyangan, 2011)
Partnership becomes one of the main asset which used by the enterprise to achievea sustainable competitive advantage. Through the partnership, the enterprise can de-velop their capabilities which cannot be developed by their own. A strategic allianceand joint venture is a popular way used by the enterprises in developing their partner-ship. Some researcher also mentioned about merger and acquisition as another formof partnership but more permanent in nature.This article specifically aim to measure a potency of partnership as a vehicle inincreasing innovation capabilities and technology within an enterprise in their effortto set up competitiveness. In particular, it is identified that a prerequisite to achieveinnovation capability and technology enhancement were depend on an ability to gain,adopt, and transfer knowledge from the partner.Keywords: partnership, innovation capabilities, technological capabilities, knowl-edge management